The Effect of Earning, Change in Account Payable, and Change in Account Receivable on Predicting Future Operating Cash Flows (Case Study on Food and Beverage Companies Listed in Indonesia Stock Exchange) - Muhammad Abdul Muis; Mery Wanialisa; Yusdianto Yusdianto (DINASTI RESEARCH, 2021)
This study aims to analyze the effect of earning, change in account payable, and change in account receivable on predicting future operating cash flows. (Case Study on food and beverage companies listed in Indonesia Stock Exchange). The research methodology used is a quantitative method with panel data and secondary data obtained from the Indonesia Stock Exchange. The sampling technique uses purposive sampling method with annual data and research period from 2013 to 2018. The data analysis technique used is panel multiple linear regression by determined the panel data regression model, normality test, classic assumption test, and hypothesis testing t-statistics test partial regression coefficients and f-statistics to examine the significance of the effects together with a significance level of 5%. The results of this study show that partially earning have a positive effect and significant and change in account payable has a negative effect and significant on predicting future operating cash flows, whereas a change in account receivable has a negative effect but non-significant on predicting future operating cash flows. Meanwhile, earnings, change in account receivable, and change in account payable together have a significant relation to future operating cash flows. The coefficient of determination from this study shows52,5%, it shows that the variation of earning, account changes receivable, and change in account payable can explain the rise and fall of future operating cash flows amounted 52.5%, while the remaining of 47.5% is affected by other factors.